El liderazgo de la secretaria ejecutiva y su influencia en el desarrollo organizacional en el Gobierno Autónomo Descentralizado Parroquial Rural de San Juan, Cantón Pueblo Viejo, de la Provincia de Los Ríos, año 2015. - Zapata García, Melania del Rocío (2015)
It is noted that the executive secretary now has become part of the structure of a company, therefore part of the organizational development of the same, it is for this reason that the theme "Leadership Executive Secretary was raised and its influence on organizational development in the Autonomous Government Decentralized Rural San Juan Parish, Pueblo Viejo, "was considered important to address this issue, since it is essential to publicize the role of the professional in society. The main objective raised in this research work, is precisely establish leadership exercised by the Executive Secretary in the Vestry Rural de San Juan Pueblo Viejo Canton, with the aim of it is determined that leadership contributes positively secretary in organizational development of the institution, which was not reflected in the results because there is no leadership and no good organizational development. The research project has been developed based on the methods applied, taking into account the primary information sources, such as surveys and interviews, which were applied to the authorities, the department heads, secretaries, administrative assistants and users Autonomous Government Decentralized Rural San Juan Parish, Pueblo Viejo. The purpose of the research work is to present the important role of executive secretary at present, but it is multifaceted and efficient as demonstrated by their profile, so it is advisable to take into consideration the information provided about to leadership and organizational development, as it is just contribute to the improvement of the corporate image of La Junta Parroquial de San Juan.